Angiogenesis within Stem Cell–Seeded Silk Scaffolds Cultured on the Chorioallantoic Membrane and Visualized by 3D Imaging. (16th May 2017) - Woloszyk, Anna; Mitsiadis, Thimios A.
Abstract: The long‐term survival and successful integration of implants for tissue replacement and regeneration highly depends upon the fast ingrowth of blood vessels from the surrounding tissues. Before selecting potential biomaterials for clinical applications, they must be thoroughly tested with proper analytical tools. This unit provides a protocol for studying the potential of cell‐seeded scaffolds to attract vessels that will form vascular networks within biomaterials. It includes seeding of stem cells into silk fibroin scaffolds, angiogenesis assay on the chorioallantoic membrane (CAM) of fertilized chicken eggs, a procedure for perfusion with MicroFil, and finally microcomputed tomography (µCT) scanning. This technique can help screen potential biomaterial implants, thereby reducing the amount of animals needed for pre‐clinical in vivo studies. © 2017 by John Wiley & Sons, Inc.